2002
DOI: 10.1002/jnr.10204
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin protects cultured cortical neurons from glutamate‐induced neurodegeneration by binding to kainate receptor

Abstract: We previously reported that arctigenin, a lignan isolated from the bark of Torreya nucifera, showed significant neuroprotective activity against glutamate-induced toxicity in primary cultured rat cortical cells. In this study, the mode of action of arctigenin was investigated using primary cultures of rat cortical cells as an in vitro system. Arctigenin significantly attenuated glutamate-induced neurotoxicity when added prior to or after an excitotoxic glutamate challenge. The lignan protected cultured neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 35 publications
0
74
0
1
Order By: Relevance
“…A previous study suggested a direct interaction between arctigenin and kainate receptors in cultured cerebrocortical neurons (Jang et al, 2002). This study demonstrated the neuroprotective effect of arctigenin in an in vitro cell culture system using kainate evoked neurodegeneration.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…A previous study suggested a direct interaction between arctigenin and kainate receptors in cultured cerebrocortical neurons (Jang et al, 2002). This study demonstrated the neuroprotective effect of arctigenin in an in vitro cell culture system using kainate evoked neurodegeneration.…”
Section: Discussionmentioning
confidence: 65%
“…Lignans are important biologically active phenolic compounds related to lignin, produced in different plants, for example in tribe Cynareae, such as Arctium, (Boldizsár et al, 2010a), Cirsium (Boldizsár et al, 2010b) species, Forsythia (Maiada et al, 1990) or Torreya (Zhao et al, 1999) (Jang et al, 2002). However, the direct effects of arctigenin on normal neuronal activity have not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Isochaihulactone (also known as K8) is a lignan compound that was identified in acetone extracts of Nan-Chai-Hu and shows antitumor activity against A549 cells in vitro and in vivo [25,26] . Lignan compounds (eg, sesamin, sesamolin) have been reported to act as neuroprotective agents against oxidative injury and excitotoxicity [27][28][29][30] . Lignans can also inhibit lipopolysaccharide-inducible COX-2 expression in macrophages [31] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the isolated compounds, arctigenin effectively inhibited the receptor binding of [ 3 H]-kainate in a competitive manner. Furthermore, it directly scavenged free radicals generated by excess glutamate (Jang et al, 2002).…”
Section: Lignansmentioning
confidence: 99%